GASTROINTESTINAL ACID-RELATED DISEASES AND ISCHEMIC HEART DISEASE: PATHOPHYSIOLOGICAL LINKS AND CLINICAL IMPLICATIONS - Raupov Abdurahmon Ortiq o’g’li (KONFERENSIYALAR, 2025)
Аnnotation. This review summarizes key evidence on the interrelations between gastroesophageal reflux disease, peptic ulcer disease, liver disorders, inflammatory bowel diseases, and ischemic heart disease. It highlights both common and specific risk factors, as well as mechanisms of comorbidity, including those linked to standard treatments. Based on meta-analyses and large- scale population studies, the review aims to support the improvement of current clinical guidelines for managing comorbid conditions.